The International Human Rights Standard and Pakistan’s Obligations regarding Wrongful Conviction: A Comparative Doctrinal Analysis with the United Kingdom - Jan, Naseem; Rajamanickam, Ramalinggam; Zahir, Mohd Zamre Mohd (Jurnal Cita Hukum, 2025)
Failures within the criminal justice system can result in wrongful convictions, leading to a loss of human rights. Additionally, wrongful convictions can erode trust in the system as a whole. This article examines the disparate human rights standards around the world as they relate to wrongful convictions, focusing on Pakistan and the expectations for Pakistan’s position in the global community on the issue. This article also examines the comparative and doctrinal position of the UK, aiming to identify the strengths and weaknesses of Pakistan's position. This takes into account the central instruments of human rights —the Universal Declaration of Human Rights and the International Covenant on Civil and Political Rights —as well as the domestic case law and statutes of both the UK and Pakistan. In Pakistan, all the agreements on fair trial and remedies under the ICCPR guarantee fair trial rights. Still, there have also been domestic legislative omissions, such as the lack of a law to compensate the wrongfully imprisoned. The UK, on the other hand, has a more systematic approach, particularly in the office of the Criminal Justice Act 1988. In light of this, Pakistan needs a domestic law that addresses the human rights standards at its disposal to deliver justice to the wrongfully convicted.